(S)-3-Hydroxybutyryl-CoA Dehydrogenase From the Autotrophic 3-Hydroxypropionate/4-Hydroxybutyrate Cycle in Nitrosopumilus maritimus - Liu, Li; Schubert, Daniel M.; Könneke, Martin; Berg, Ivan A. (Frontiers in Microbiology, 2021)
Ammonia-oxidizing archaea of the phylum Thaumarchaeota are among the most abundant organisms that exert primary control of oceanic and soil nitrification and are responsible for a large part of dark ocean primary production. They assimilate inorganic carbon via an energetically efficient version of the 3-hydroxypropionate/ 4-hydroxybutyrate cycle. In this cycle, acetyl-CoA is carboxylated to succinyl-CoA, which is then converted to two acetyl-CoA molecules with 4-hydroxybutyrate as the key intermediate. This conversion includes the (S)-3-hydroxybutyryl-CoA dehydrogenase reaction. Here, we heterologously produced the protein Nmar_1028 catalyzing this reaction in thaumarchaeon Nitrosopumilus maritimus, characterized it biochemically and performed its phylogenetic analysis. This NAD-dependent dehydrogenase is highly active with its substrate, (S)-3-hydroxybutyryl-CoA, and its low Km value suggests that the protein is adapted to the functioning in the 3-hydroxypropionate/4-hydroxybutyrate cycle. Nmar_1028 is homologous to the dehydrogenase domain of crotonyl-CoA hydratase/(S)-3-hydroxybutyryl-CoA dehydrogenase that is present in many Archaea. Apparently, the loss of the dehydratase domain of the fusion protein in the course of evolution was accompanied by lateral gene transfer of 3-hydroxypropionyl-CoA dehydratase/ crotonyl-CoA hydratase from Bacteria. Although (S)-3-hydroxybutyryl-CoA dehydrogenase studied here is neither unique nor characteristic for the HP/HB cycle, Nmar_1028 appears to be the only (S)-3-hydroxybutyryl-CoA dehydrogenase in N. maritimus and is thus essential for the functioning of the 3-hydroxypropionate/4-hydroxybutyrate cycle and for the biology of this important marine archaeon.